Exploring the interrelationship between the skin microbiome and skin volatiles: A pilot study - Haertl, Tobias; Owsienko, Diana; Schwinn, Leo; Hirsch, Cathrin; Eskofier, Bjoern M.; Lang, Roland; Wirtz, Stefan; Loos, Helene M. (Frontiers in Ecology and Evolution, 2023)
Unravelling the interplay between a human’s microbiome and physiology is a relevant task for understanding principles underlying human health and disease. With regard to human chemical communication, too, it is of interest to elucidate the role of the microbiome in shaping or generating the human volatilome and body odors. In this study, we characterized the microbiome and volatiles sampled from the neck and axilla of ten participants (five male, five female) on two sampling days, by applying different methodological approaches. Volatiles emitted from the respective skin site were collected using textile sampling material and analyzed on two analytical columns with varying polarity of the stationary phase. Microbiome samples were analyzed by a culture approach coupled with MALDI-TOF-MS analysis and a 16S ribosomal RNA gene (16S RNA) sequencing approach. Statistical and advanced data analysis methods revealed that classification of body sites was possible by using volatilome and microbiome data sets, respectively. Higher classification accuracy was achieved by combination of both data pools. The investigation of microbiome and volatilome interactions proved to be challenging due to the limited data set and lack of quantitative data. However, the interdisciplinary methodological platform developed here will enable further investigations of skin microbiome and skin volatilome alterations in physiological and pathological conditions.